Deriving organ doses for medical radiation workers using personal monitoring data with a focus on lung. (NCPR commentary ;, 2020)
"The purpose of this Commentary is to describe an optimum approach for using personal monitoring data to estimate lung and other organ doses. The Commentary highlights specific precautions applicable to epidemiologic study of medical radiation workers. Such guidance is important as organ doses, along with associated epidemiologic analyses for both female and male populations are necessary to assist the National Aeronautics and Space Administration's need to assess sex-specific lung cancer risks and radiation limits currently in place for female astronauts noting differences between the medical and space radiation environments"--